The Making of the modern body : sexuality and society in the nineteenth century - Gallagher, Catherine; Laqueur, Thomas Walter (Representations Bks., 1987)
Scholars have only recently discovered that the human body itself has a history. Not only has it been perceived, interpreted, and represented differently in different epochs, but it has also been lived differently, brought into being within widely dissimilar material cultures, subjected to various technologies and means of control, and incorporated into different rhythms of production and consumption, pleasure and pain. The eight articles in this volume suppor.